The ultimate scholarship book, 2015 : billions of dollars in scholarships, grants and prizes - Gen, Kelly Tanabe (U.S.A. : Super College, LLC, 2015)
"Information on 1.5 million scholarships, grants, and prizes is easily accessible in this revised directory with more than 300 new listings that feature awards indexed by career goal, major, academics, public service, talent, athletics, religion, ethnicity, and more. Each entry contains all the necessary information for students and parents to complete the application process, including eligibility requirements, how to obtain an application, how to get more information about each award, sponsor website listings, award amounts, and key deadlines. With scholarships for high school, college, graduate, and adult students, this guide also includes tips on how to conduct the most effective search, how to write a winning application, and how to win the scholarships you find!, "--Amazon.com.
How to use the ultimate scholarship book -- Where to find the best scholarships -- How to win the scholarships you find -- How to write a scholarship essay -- The scholarship resume -- Getting great recommendations -- Ace the scholarship interview -- Final thoughts -- The ultimate scholarship directory.
Includes indexes.
DELL.
Keywords: Scholarships -- United States -- Directories; Student aid -- United States -- Directories